2011
DOI: 10.1007/s10339-011-0395-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of narrowing the base of support on the gait, gaze and quiet eye of elite ballet dancers and controls

Abstract: We determined the gaze and stepping behaviours of elite ballet dancers and controls as they walked normally and along progressively narrower 3-m lines (l0.0, 2.5 cm). The ballet dancers delayed the first step and then stepped more quickly through the approach area and onto the lines, which they exited more slowly than the controls, which stepped immediately but then slowed their gait to navigate the line, which they exited faster. Contrary to predictions, the ballet group did not step more precisely, perhaps d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…By foveating the door edges, the participants were better able to attend to the doors’ positions, while short fixation durations allowed the participants to process each door’s location more frequently. The differences in spatio-temporal patterns of fixation while walking or using a wheelchair seem to be similar to those between elite and non-elite athletes (Kato and Fukuda, 2002; Martell and Vickers, 2004; Nagano et al, 2004; Panchuk and Vickers, 2011), in that non-elite participants showed shorter fixation and more frequent saccades at critical moments.…”
Section: Gaze Behavior During Adaptive Locomotionmentioning
confidence: 59%
“…By foveating the door edges, the participants were better able to attend to the doors’ positions, while short fixation durations allowed the participants to process each door’s location more frequently. The differences in spatio-temporal patterns of fixation while walking or using a wheelchair seem to be similar to those between elite and non-elite athletes (Kato and Fukuda, 2002; Martell and Vickers, 2004; Nagano et al, 2004; Panchuk and Vickers, 2011), in that non-elite participants showed shorter fixation and more frequent saccades at critical moments.…”
Section: Gaze Behavior During Adaptive Locomotionmentioning
confidence: 59%
“…Drawing on the postural-stability approach (cf. Panchuk & Vickers, 2011; Rienhoff et al, 2012), performance-enhancing effects should be found as a function of final-fixation onset only, with an earlier fixation onset due to the longer period of postural stabilization, resulting in better performance. In contrast, drawing on the optimized movement parameterization approach, two other result patterns could be predicted, namely, (a) a main effect for target onset with an earlier target onset due to the increase in visual processing time, resulting in better performance.…”
Section: Methodsmentioning
confidence: 98%
“…These results lead the authors to the conclusion that the functionality of the QE might be less rooted in information processing. Instead, Rienhoff et al (2012)—because direct measures of postural stability were not applied—speculated that the QE might optimize postural control by linking eye to head and body movements (see also Panchuk & Vickers, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quiet Eye is specified by the final visual fixation or tracking gaze on a specific location or object in the performance space that lasts for a minimum of 100 ms prior to the onset of the movement action (Vickers, 1996;2007). Quiet Eye has been associated with higher levels of skill and performance in a myriad of performance activities-e.g., golf putting, stopping a hockey puck, or shooting a basketball in sport (Panchuk et al, 2014;Panchuk & Vickers, 2006;Klostermann et al, 2017), locomotion and balance (Panchuk & Vickers, 2011), precise surgical dissection in medicine (Harvey et al, 2014), rehabilitation of children with developmental coordination disorder (Miles et al, 2015), and decision making and subsequent inhibition or targeted firing of a firearm in law enforcement (Vickers & Lewinski, 2012). Quiet Eye is also sensitive to psychological factors such as anxiety and arousal in these task contexts (Vickers & Williams, 2007;Vine & Wilson, 2011).…”
mentioning
confidence: 99%